Integrating Zakat and Social Work as the Bedrock of Reducing Poverty in Kano State - Muhammad Aliyu Dalhat (IAIN Syekh Nurjati Cirebon, 2026)
This study examines the integration of zakat and social work as a foundational approach to poverty reduction in Kano State, Nigeria, where more than 60% of the population lives below the poverty line, despite zakat collections estimated at approximately 10 billion annually. Employing a descriptive survey design with stratified random sampling, data were collected from 384 respondents across nine local government areas. The study assessed the effectiveness of zakat distribution, the role of social work interventions, and the potential impact of their integrated application using a validated research instrument (IZSWOPAKS; Cronbach's alpha = 0.81). Data were analyzed using descriptive statistics and Chi-square tests at the p < 0.05 significance level. The findings revealed persistent inefficiencies in zakat distribution, particularly in terms of timeliness, adequacy, and transparency. Respondents overwhelmingly expressed strong support for integrating zakat and social work, citing improved targeting of beneficiaries, more holistic support mechanisms, and greater prospects for sustainable poverty alleviation. The study concludes that integrating zakat's faith-based redistributive framework with professional social work practices offers a more effective and sustainable strategy for poverty reduction in Kano State. This study recommends structured institutional collaboration between zakat management bodies and social work institutions to strengthen and enhance economic empowerment initiatives.